1985
DOI: 10.1038/sc.1985.6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy of an alpha-I-adrenergic blocker in the slow calcium channel blocker in the control of autonomic dysreflexia

Abstract: Cystometry, using a portable CO2 cystometer, is a convenient method for detecting autonomic dysreflexia (A.D.) in response to bladder distention. Serial tracings on successive days were found to be consistent. This method was used to compare the effect of the antihypertensive drugs, phenoxybenzamine and nifedipine, in modifying the blood pressure responses of 12 tetraplegic patients. Given as regular medication twice daily, neither drug was effective in preventing A.D. responses to bladder filling, and a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 3 publications
(1 reference statement)
1
18
0
Order By: Relevance
“…Treatment options for AD are well established: removal of the triggering factor and if required symptomatic therapy using alpha-receptor blocker 24,25 or calcium-channel blocker. 26 In the present study, the intravenous application of the alpha-blocking agent phentolamine lowered the resting BP and increased the resting HR. During stimulation, the maximum BP increase was significantly reduced and severe hypertension prevented.…”
Section: Discussionsupporting
confidence: 52%
“…Treatment options for AD are well established: removal of the triggering factor and if required symptomatic therapy using alpha-receptor blocker 24,25 or calcium-channel blocker. 26 In the present study, the intravenous application of the alpha-blocking agent phentolamine lowered the resting BP and increased the resting HR. During stimulation, the maximum BP increase was significantly reduced and severe hypertension prevented.…”
Section: Discussionsupporting
confidence: 52%
“…Dykstra et al 41 studied the effect of sublingual nifedipine during cystoscopy and found that it significantly decreased mean SBP and diastolic blood pressure (DBP). Lindan et al 42 similarly found that it decreased blood pressure within 30-40 min. Thyberg et al 43 showed that prophylactic nifedipine significantly reduced maximum SBP and DBP, and blood pressure during cystometry.…”
Section: Treatment Of Ad During Other Ad Triggering Proceduresmentioning
confidence: 87%
“…Krassioukov et al, 33 however, mention that there is conflicting evidence on its effectiveness. Lindan et al 42 compared it with nifedipine in prophylaxis during cystometry and found that both drugs reduced resting blood pressure, but failed to prevent AD during bladder distension. Both medications caused hypotension at rest, requiring discontinuation of treatment or reduction of dose in some participants.…”
Section: Treatment Of Ad In Other Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sublingual administration of nifedipine seems to be effective in the prevention of an expected attack, eg during cystoscopy, but methodological problems, like small numbers of comparable measure ments, lack of standardised stimuli and unspecified intervals of blood pressure measurement make the interpretation of previous studies difficult. [2][3][4][5] We have previously described the blood pressure response in repeated cystometries, and the aim of this study was to evaluate the effect of nifedipine with this improved technique.…”
Section: Introductionmentioning
confidence: 99%